Gathering Nutritious Edible Wild Plants Based on Societies Indigenous Knowledge from Sempolan, Jember Regency - Kuswati Kuswati; Widi Cahya Adi (Jurnal Biologi Tropis, 2021)
Indonesia, as a mega biodiversity country, has various types of wild plants. Sempolan Village, part of Jember Regency, has fertile land to support the growth of a wild plant. This research investigates wild plants used as food sources by indigenous peoples in Plalangan, Sempolan Village. This study also conducts data on how wild plants were cooked, served, and enriched by nutrition notice. The method is qualitative descriptive analysis obtained from observation, interview, documentation, and literature study. So, research results found 26 species and grouped them into 19 families. In addition, the locality of these species is in yards, fields, and roadsides. The habitus identified is an herb (77%), tree (11%), shrub (8%), and liana (4%). Those foods categorize into 1) carbohydrates sources, 2) vegetables, and 3) fresh fruits. The carbohydrate sources mostly served as a side dish, compote, and flour by stewing and frying. The vegetables include 18 species served as complements of the main menu, which cooked for soup, curry, stir fry, ointment, and pothok. Fresh fruits comprise of 4 speciesÃÂ were directly consume or make a salad. Furthermore, all food resources contain essential nutrients like vitamins, macro and micro minerals, and phytochemicals that are important for society's growth and healthy lives. Finally, Information on wild plants as a food source will increase food diversification as well as dishes.